Stage and sex-dependent responses of immature predatory mites (Blattisocius dentriticus) to predation risk from cannibalistic conspecifics. (December 2022) - Gu, Xinyao; Li, Guang-Yun; Zhang, Zhi-Qiang
Abstract: Blattisocius dendriticus (Acari: Blattisociidae) is a predatory gamasid mite with the potential for the biological control of mites attacking stored products. However, its interactions with its cannibalistic conspecifics are poorly understood. In this study, we determined the effects of predation risk from cannibalistic conspecifics on the survival, development, prey consumption, and behaviour of the predator by comparing the performance of predators exposed to cues from their conspecifics with their counterparts exposed to cues of their prey and the prey food source. The results show that the survivorship of immature predators was similar across treatments. However, predators under cannibalistic risks extended the duration of their immature stages due to a prolonged protonymphal stage. Moreover, the effects of predation risk were also sex-specific, with the males responding to the risk of cannibalism, but not the females. By highlighting the non-consumptive effects of cannibalistic conspecifics on predators associated with sex and maternal age, the present study improves our understanding of the indirect effects of cannibalism and its interactions with other factors, which may affect the performance of B. dentriticus as a biological agent. Highlights: Cannibalistic risk as a unique form of predation risk showed profound influence on the life-history traits of predatory mites in their early life. In the protonymphal stage, predatory mites exposed to cannibalistic risk showed significantly longer developmental periods. The cannibalistic risk induced responses were sex-specific, with males extending their protonymphal stage and being more active, but not the females.